The Effect of Aphasia on Sixty Six Years Old in Language Acquisition - Daulay, Sholihatul Hamidah; Ningsih, Fitri Randia; Satria, Willy; Arlina, Arlina; Arsini, Yenti (SPHOTA: Jurnal Linguistik dan Sastra, 2024)
This study aimed to describe language impairments (motor aphasia). The specific goals of the study include describing motor aphasia-related language impairments, their etiology, and the use of language by those who have these disorders (motor aphasia). In this study, the author discussed the effects of Aphasia on grandmother in language acquisition. In this study, the author observed the language of a grandmother who is 66 years old. This research was conducted in Medan. The grandmother who was a participant in this study was named Zaimah Kusuma. She has dementia in her language due to her old age. The researcher conducted this research using descriptive qualitative method. Data collection was taken by interview, recording, and documentation. Dementia is a disease that causes loss of memory and the ability to think. These conditions have an impact on the patient's lifestyle, social skills, and daily activities. According to the study's findings, the 66-year-old aphasia patients who were its participants are capable of speaking simple words, questions, and instructions. 66 years old aphasic patients can typically pronounce sentences with the pattern S-P, P-S, and P-K